The experiences of Chinese mainland students with English-medium instruction in a Macau University. Issue 3 (27th May 2018) - Wang, Yan; Yu, Shulin; Shao, Yanju
Abstract: While research on English-medium instruction (EMI) has proliferated in the past decades, little research has examined how students from a monolingual background actually experience EMI, or the learning processes involved in such experiences. Drawing upon in-depth interviews and student reflection journals, this study examines the experiences of Chinese university students currently studying in an EMI university in Macau. The findings show that while the students were satisfied with their learning in the EMI context, and they all expressed a perceived necessity for EMI, EMI presented major challenges to their learning and increased their study burden, and the students had experienced numerous frustrations, difficulties and challenges in the transition from the CMI context to the EMI context. The findings also indicate that the students took various measures to address these difficulties and frustrations. This study can provide a better understanding of the real learning needs of Chinese students in an EMI context, and the strategies used by them to address the difficulties and challenges experienced in the transition from the CMI context to the EMI context.